2014
DOI: 10.1038/gene.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

BXSB-type genome causes murine autoimmune glomerulonephritis: pathological correlation between telomeric region of chromosome 1 and Yaa

Abstract: The autoimmune-prone BXSB/MpJ-Yaa mouse is a model of membranous proliferative glomerulonephritis (MPGN). Severe MPGN has been reported only in male BXSB/MpJ-Yaa mice because of the Y-linked autoimmune accelerator (Yaa) locus. However, we show that female BXSB/MpJ mice develop age-related MPGN without Yaa. Female BXSB/MpJ mice clearly developed MPGN characterized by increased mesangial cells, thickening of the glomerular basement membrane (GBM), double contouring and spike formation of GBM with T-cell infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…7 Furthermore, we recently reported that not only male BXSB/MpJ-Yaa mice, but also female BXSB/MpJ mice, clearly exhibit symptoms of age-related autoimmune disease onset, such as increased spleen weights, elevated serum autoantibodies and glomerulonephritis, without the contribution of the Yaa mutation. 44,45 For the BXSB/MpJ strain, age-related autoimmune disease onset was attributed to the expression of immune-associated genes in the telomeric regions of chromosome 1. 45 Therefore, gene mutations as well as genetic backgrounds associated with the immune response may also be important in the development of MFALCs and lung cellular infiltration in murine autoimmune disease models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Furthermore, we recently reported that not only male BXSB/MpJ-Yaa mice, but also female BXSB/MpJ mice, clearly exhibit symptoms of age-related autoimmune disease onset, such as increased spleen weights, elevated serum autoantibodies and glomerulonephritis, without the contribution of the Yaa mutation. 44,45 For the BXSB/MpJ strain, age-related autoimmune disease onset was attributed to the expression of immune-associated genes in the telomeric regions of chromosome 1. 45 Therefore, gene mutations as well as genetic backgrounds associated with the immune response may also be important in the development of MFALCs and lung cellular infiltration in murine autoimmune disease models.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 For the BXSB/MpJ strain, age-related autoimmune disease onset was attributed to the expression of immune-associated genes in the telomeric regions of chromosome 1. 45 Therefore, gene mutations as well as genetic backgrounds associated with the immune response may also be important in the development of MFALCs and lung cellular infiltration in murine autoimmune disease models.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA (2 µg) was reverse-transcribed with SUPERSCRIPT RT using oligo dT as primer to synthesize first-strand cDNA in 20-µl volume according to manufacturer’s instructions (Invitrogen, Waltham, MA). The primers used for the qRT-PCR for the interferon activated gene 202B ( Ifi202b ) gene were synthesized (Sigma) using sequences obtained from the published literature (forward: 5′-GGCAATGTCCAACCGTAACT-3′ and reverse: 5′-TAGGTCCAGGAGAGGCTTGA-3′) (Kimura et al 2014) and the primers for apolipoprotein A135 II ( Apoa2 ) gene were proprietary (PPM05347B, Qiagen). The real-time PCR reaction was carried out in a 25-µl volume in 1x SYBR Green PCR core reagents (Qiagen) containing 1 µl cDNA template diluate (1:5, v/v) and 6 pmol primers using the StepOne™ Real-Time PCR system (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…This genetic source of diversity can be ultimately ascribed to a number of possible genetic alterations/variations including polymorphic alleles, unique quantitative trait loci (QTL) intervals, or specific haplotypes. [28][29][30][31][32][33][34][35][36] The influence of the inbred genetic background pervades many if not all the experimental contexts considered in this review.…”
Section: Inbred Mouse Strains: Immune Relevant Genotypes and Phenotypesmentioning
confidence: 99%
“…111 Spontaneous lupus-like conditions in mice are associated with mutations such as Fas lpr and Yaa and are influenced by genetic background. [28][29][30][31][32][33][34][35][36] Inbred strains that spontaneously develop lupus-like conditions include MRL/MpJ, BXSB/MpJ, NZB, NZW, NZBWF1 (aka NZB/W), NZM2410, and Palmerston North (PN/nBSwUmabJ). 112,63,113,114 MRL/MpJ inbred mice are autoimmune prone and spontaneously develop an autoimmune phenotype as they age.…”
Section: Influence Of Genetic Backgroundmentioning
confidence: 99%